(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the importance of examples of folk art in developing students’ artistic thinking and the pedagogical issues in this process. Folk oral art is considered an important tool in shaping students’ creative thinking, aesthetic taste, and logical reasoning abilities. However, there are existing problems in the modern educational process, such as the insufficient attention given to folk art, the dominance of digital technologies, and the lack of innovative approaches. The article suggests ways to integrate folk art examples into the educational system, including the use of interactive methods, digital technologies, and cultural-educational projects to address these issues.